2018
DOI: 10.13057/biodiv/d190130
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and soil conservation of degraded land using sengon (Falcataria moluccana) and peanut (Arachis hypogaea) agroforestry system

Abstract: Sarminah S, Karyati, Karmini, Simbolon J, Tambunan E. 2018. Rehabilitation and soil conservation of degraded land using sengon (Falcataria moluccana) and peanut (Arachis hypogaea) agroforestry system. Biodiversitas 19: 222-228. Rehabilitation and soil conservation effort on degraded lands is not always a success. Multiple factors, such as the field’ biogeophysical conditions and the choice of suitable plant species determine the effectivity of the rehabilitation program. Our research aimed to implement agrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 3 publications
(3 reference statements)
1
15
1
2
Order By: Relevance
“…The soil erosion rates recorded in the current study was lower than the values reported for some other agroforestry systems (Karyati et al 2018;Sarminah et al 2018;Sumarno et al 2011) as presented in Table 8. This result implied that the combination of vegetative (F. moluccana and V. cylindrica) and terrace system could be effectively implemented in different sloping lands.…”
Section: Planting System Erosioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The soil erosion rates recorded in the current study was lower than the values reported for some other agroforestry systems (Karyati et al 2018;Sarminah et al 2018;Sumarno et al 2011) as presented in Table 8. This result implied that the combination of vegetative (F. moluccana and V. cylindrica) and terrace system could be effectively implemented in different sloping lands.…”
Section: Planting System Erosioncontrasting
confidence: 72%
“…The average diameter increment of F. moluccana in F. moluccana and V. cylindrica agroforestry system (on steep and very steep slopes) was lower than those in F. moluccana and Arachis hypogaea agroforestry system (on slight steep and steep slopes) as reported by Sarminah et al (2018). On the contrary, the average height increment of this combination was higher than those reported by Sarminah et al (2018). Similarly, the diameter increment of F. moluccana in this study was also lower than those in agroforestry system, monoculture system, and intensive monoculture system (Swestiani and Purwaningsih 2013; Wahyudi and Panjaitan 2013).…”
Section: Silvicultural Aspectssupporting
confidence: 58%
See 2 more Smart Citations
“…Kerusakan hutan akibat tata guna lahan memengaruhi struktur dan komposisi vegetasi, yang selanjutnya dapat mengarah pada pembentukan lahan yang tidak produktif. Lahan yang mengalami degradasi ini menjadi semakin kritis karena erosi yang dipicu oleh aktivitas manusia yang ceroboh dan tidak bertanggung jawab (Sarminah, Karyati, Karmini, Simbolon, & Tambunan, 2018). Curah hujan merupakan faktor penting yang berkontribusi terhadap erosi (Liu, Liu, & Zhu, 2018).…”
Section: Pendahuluanunclassified